STUDI KOMPARASI PRESTASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN MAKE A MATCH (MM) PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X SMA NEGERI 4 PEKANBARU - Dewi Sartika Asril; Johni Azmi; R.Usman Rery (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This Research aims to achieve Student competence about Atom Structure on X class SMA Negeri 4 Pekanbaru by Applicatings strategy of active learning Numbered Head Together (NHT) type and Make A Match (MM) type. This research type is experiment research with pretest design and posttest. Research starts from July 21 – August 31, 2015. This research population is student X class SMA Negeri 4 Pekanbaru that consist of 10 class and its sample is taken within homogenity, and taken 3 class with similar distribution result. Data analysis techniques include test requirements analysis and hypothesis testing. Based on the calculation formula hypothesis testing using analysis of variance (ANOVA or ANOVA), found that the value of Fcount than Ftable is 8.340> 3.09. So it can be interpreted that the null hypothesis is rejected or accepted the hypothesis of this research, that there is a significant difference between the average (mean). To know that there are significant differences among the three groups, it can be followed by Tukey's test. Based on the calculations, the value of Tukey's HSD is 11.129. The comparation results obtained X1 ≠ X2 Since 18.5> 11.129, X1 = X3 Because 5.028 <X3 ≠ X2Karena 11.129 and 13.472> 11.129. Then, the use of active learning model NHT and MM can improve student achievement seen the failure by students achieve mastery learning on the subject of Atom Structure in class X of SMA Negeri 4 Pekanbaru.Keywords : Numbered Head Together (NHT), Make a Match (MM), Atom Structure.